2022
DOI: 10.1007/s11666-022-01504-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Direct Metal Deposition Processes Using High-Resolution In-line Atomic Emission Spectroscopy

Abstract: Process monitoring and control methods during direct metal deposition (DMD) ensure consistent manufacturing quality of the product. Naturally occurring optical process emissions provide selective and specific element lines, which can be investigated by optical spectrometers. However, DMD processes are mainly characterized by thermal conduction. Hence, the resulting optical emission lines have low intensities. The aim of this work is to investigate the spectral lines and determine the required resolution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Numerous experiments have shown that radiation measurement is well suited as a contactless temperature measurement technique to monitor melt pool characteristics during the PBF-LB/M process [5,6] as well as other AM processes, e.g., direct metal deposition (DMD) [7][8][9][10]. One of the fundamental laws of radiation measurement technology is Planck's radiation law [11], given in Equation (1).…”
Section: Radiation Measurement Technologymentioning
confidence: 99%
“…Numerous experiments have shown that radiation measurement is well suited as a contactless temperature measurement technique to monitor melt pool characteristics during the PBF-LB/M process [5,6] as well as other AM processes, e.g., direct metal deposition (DMD) [7][8][9][10]. One of the fundamental laws of radiation measurement technology is Planck's radiation law [11], given in Equation (1).…”
Section: Radiation Measurement Technologymentioning
confidence: 99%